Mengoptimalisasi Styling Pada Aplikasi Help Desk - Salsabila, Zerina Nur Salsabila; I Gusti Ngurah Anom Cahyadi Putra; Ida Ayu Gde Suwiprabayanti Putra (Jurnal Pengabdian Informatika, 2026)
The optimization of the Help-Desk application's interface styling was carried out to enhance its responsiveness, modern appearance, and user comfort. The scope of this activity includes redesigning the user interface (UI), improving layout structure, and applying responsive design principles to ensure optimal usability across various devices. The process involved user needs analysis, interface design using Figma, development of an interactive prototype that represents the application's workflow, and design evaluation by internal users. The results showed an increase in positive user perception regarding the application's appearance, readability, and navigation. In addition to enhancing the application's professional impression, the new design is also expected to support user productivity in performing daily tasks through the Help-Desk system. The validated final design is ready to be used as a visual guideline for future application development in a more efficient and standardized manner